2017
DOI: 10.1111/jch.13136
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related relationships between uric acid and target organ damage in hypertension

Abstract: Heterogeneous results have been obtained in the relationship between serum uric acid (SUA) and target organ damage (TOD) in patients with hypertension. Clinic blood pressure, SUA, and cardiac, arterial (carotid and aortic), and renal TOD were assessed in 762 consecutive patients with hypertension. Hyperuricemia was defined as an SUA >7.0 in men and >6.0 mg/dL in women. Men with hyperuricemia compared with those with normal SUA showed lower estimated glomerular filtration rates and E/A ratios and a higher preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…We found a negative association between BQI score and serum uric acid levels albeit no with other cardiometabolic risk markers such as lipid, glycemic profile, or metabolic syndrome. Previous research showed that serum uric acid is related to cardiovascular disease [ 42 , 43 ], which in turn is an independent predictor for future cardiovascular mortality [ 44 ]. Milk proteins seem to decrease serum uric acid concentration in adults [ 45 ] and as BQI scored positively with the presence of dairy products in the meal, they could be one of the responsible components.…”
Section: Discussionmentioning
confidence: 99%
“…We found a negative association between BQI score and serum uric acid levels albeit no with other cardiometabolic risk markers such as lipid, glycemic profile, or metabolic syndrome. Previous research showed that serum uric acid is related to cardiovascular disease [ 42 , 43 ], which in turn is an independent predictor for future cardiovascular mortality [ 44 ]. Milk proteins seem to decrease serum uric acid concentration in adults [ 45 ] and as BQI scored positively with the presence of dairy products in the meal, they could be one of the responsible components.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many other risk components, such as inflammatory markers, microalbuminuria, hyperuricemia, and disorders of coagulation, have been debated regarding whether to be included in the MetS definition [ 8 , 9 , 10 , 11 , 12 ]. A novel study brings data on the role of Uric Acid (UA) in the development of renal alteration [ 13 ]. The incidence of MetS are increasing worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…UA has been also identified as a potential factor concurring in the development and/or progression of preclinical TOD. Regarding arterial stiffness, this association has been evaluated in numerous cross‐sectional studies; however, these studies frequently provided heterogeneous results . Furthermore, to the best of our knowledge, only three published paper have evaluated the relationship between UA and PWV in prospective cohort …”
Section: Introductionmentioning
confidence: 99%